Sprobuj szczescia!!! (Elbląg : [s.n.], 1946)
Afisz inf. o loterii 13.10.1946 r.
Brak pol. znaków.
Keywords: Loterie -- Polska -- Elbląg -- 1945-1970 -- druki ulotne; Elbląg (Polska) -- 1945-1970 -- druki ulotne